2018
DOI: 10.1007/s10995-018-2441-1
|View full text |Cite
|
Sign up to set email alerts
|

Social Factors Associated with Non-initiation and Cessation of Predominant Breastfeeding in a Mother–Child Cohort in Spain

Abstract: Objective The aim of the study was to identify factors associated with non-initiation and cessation of predominant breastfeeding (PBF) in a mother-child cohort from Spain. Materials and Methods The analysis included 2195 mother-infant from birth to 14 months post- delivery recruited between 2004 and 2008. Maternal characteristics were collected during the pregnancy. Lactation data were obtained at 6 and 14 months after delivery. PBF was defined as intake of breast milk plus liquids like juices or water. The PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 31 publications
2
17
0
5
Order By: Relevance
“…(21,26) Having breastfed other children helps women face the first days of adaptation with the newborn more easily, which favors a long-lasting breastfeeding. (20,21) Regarding women's physical aspects, the present study showed that most women had protruding nipples, a characteristic that was associated with the breastfeeding practice. This finding helps support the evidence that the nipple anatomy can influence the difficulties experienced in the beginning of the breastfeeding period, especially when it is malformed and/or underdeveloped, which usually hinders latch and its maintenance, influencing the practiced type of breastfeeding.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…(21,26) Having breastfed other children helps women face the first days of adaptation with the newborn more easily, which favors a long-lasting breastfeeding. (20,21) Regarding women's physical aspects, the present study showed that most women had protruding nipples, a characteristic that was associated with the breastfeeding practice. This finding helps support the evidence that the nipple anatomy can influence the difficulties experienced in the beginning of the breastfeeding period, especially when it is malformed and/or underdeveloped, which usually hinders latch and its maintenance, influencing the practiced type of breastfeeding.…”
Section: Discussionmentioning
confidence: 56%
“…Studies reported that early weaning is more common among younger women (< 20 years) than among older women (>30 years). (20,21) This divergence may be explained by the higher number of women undergoing exclusive breastfeeding who had already had a breastfeeding experience.…”
Section: Discussionmentioning
confidence: 99%
“…Creating more breastfeeding‐friendly workplaces is especially important because a recent study in Spain has concluded that a decrease in predominant breastfeeding rates can be partly attributed to women's returning to work. The authors of that study posited that until employers develop policies that encourage breastfeeding, the recommended 6‐month breastfeeding period by WHO is unlikely to be achieved by most working women (Villar et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among several determinants, increasing attention has been paid to return to work (RTW) as a major constraint to initiate and continue BF [2][3][4]. Numerous previous studies consistently concluded that RTW before 12-16 weeks, compared with later or not at all, was associated with shorter BF duration [5][6][7][8][9][10][11][12][13][14][15]. Indeed, women themselves mentioned RTW as a reason for stopping BF [16][17][18][19][20], though not in all settings [21,22], probably due to cultural norms and work support backgrounds.…”
Section: Introductionmentioning
confidence: 99%